Antimicrobial activity of Austroeupatorium inulaefolium (H.B.K.) against intracellular and extracellular organisms. Issue 23 (2nd December 2018) - Bua, A.; Usai, D.; Donadu, M. G.; Delgado Ospina, J.; Paparella, A.; Chaves-Lopez, C.; Serio, A.; Rossi, C.; Zanetti, S.; Molicotti, P.
Abstract: The antimicrobial activity of Austroeupatorium inulaefolium (H.B.K.) essential oil was studied in different pathogens species and its cytotoxicity activity was determinated on different cellular lines. Despite the good antibacterial activity of A. inulaefolium, it has been cytotoxic at low concentrations. Consequently it might be interesting to determine the antimicrobial activity and cytotoxicity of the major compounds of this essential oil. Abstract :